Effect of spin-orbit field on magnetization reversal in GaMnAs single layers with 4-fold in-plane magnetic anisotropy - Kyoul Han; Kyung Jae Lee; Sanghoon Lee; Xinyu Liu; M. Dobrowolska; Jacek K. Furdyna (AIP Advances, 2023)
Effect of spin-orbit-induced (SOI) field on magnetization reversal in ferromagnetic semiconductor GaMnAs films with 4-fold in-plane magnetic anisotropy has been investigated by planar Hall resistance (PHR) and anisotropic magnetoresistance (AMR) with current along the <110> and <100> crystallographic directions, respectively. Field scan hysteresis of PHR and AMR measured with current of 2.5 mA were observed to be asymmetric respect to zero field, showing different transition fields between positive and negative field regions. In addition, the hysteresis asymmetry is reversed as the sign of the current is reversed from positive to negative. Such dependence of asymmetry on current polarity implies that the current-induced spin-orbit field, which is known to depend on the current direction, significantly affects magnetization reversal. The asymmetry observed for currents along [100], [010], [110], and [11̄0] crystallographic directions is fully consistent with the effects arising from the Dresselhaus-type SOI fields in GaMnAs films.